Leave policies in Europe: current policies, future directions. Issue 5 (24th September 2019) - Moss, Peter; Deven, Fred
Abstract : Purpose: The purpose of this paper is to review the development of leave policies in Europe, both at a regional and national level, and to consider what future directions such policies might take to meet changing conditions and emerging needs. Design/methodology/approach: The paper draws on the work of an international network that the authors founded in 2004, which brings together experts on leave policy from over 40 countries, and in particular on an annual review of national leave policies conducted by network members. Findings: The article presents developments in European legislation on leave policy stretching from 1883 to the present day, and outlines the extent of leave policies in European countries and the wide variations in the design of these policies. It suggests that future directions in leave policy need to address the relationship between this and other policy areas; the need for a life course perspective to leave policy, getting beyond parental leave; and that leave should turn away from being considered an employment benefit towards becoming a universal right to care. Originality/value: The paper provides a concise overview of leave policy in the global region where leave policies began and are today most developed, at both a regional and national level. It is also intended to stimulate debate about the future directions that leave policy might take.